2015
DOI: 10.1007/s13277-015-4558-9
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-144 mediates metabolic shift in ovarian cancer cells by directly targeting Glut1

Abstract: Warburg effect is characterized by an increased utilization of glucose via glycolysis in cancer cells, even when enough oxygen is present to properly respire. Recent studies demonstrate that deregulation of microRNAs contributes to the Warburg effect. In the present study, we show that miR-144 is downregulated while glucose transporter 1 (Glut1) is upregulated in ovarian cancers. In vitro studies further showed that miR-144 inhibits Glut1 expression through targeting its 3'-untranslated region. As a result, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In fact, several other miRs were also found to be involved in the regulation of glycolysis in human cancers. For instance, overexpression of miR-144 enhanced glucose uptake and lactate production in ovarian cancer cells, leading to a rapid growth of ovarian cancer cells (28). Xu et al (29) reported that inhibition of miR-340 increased Glut1 expression, leading to an increase in lactate secretion and glucose uptake rate.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several other miRs were also found to be involved in the regulation of glycolysis in human cancers. For instance, overexpression of miR-144 enhanced glucose uptake and lactate production in ovarian cancer cells, leading to a rapid growth of ovarian cancer cells (28). Xu et al (29) reported that inhibition of miR-340 increased Glut1 expression, leading to an increase in lactate secretion and glucose uptake rate.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) have recently been described as important players in human cancer, and some are believed to be potential therapeutic targets. Expression of microRNAs is markedly deregulated in ovarian cancer, which strongly suggests that miRNAs are involved in the pathogenesis of ovarian cancer (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). In the present study, we identified the deregulation of miR-106a in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Direct targeting of the insulin receptor substrate 1 (IRS-1) by miR-144, one of the miRNA with increased expression in T2D patient and HFD/STZ rats, has been validated by luciferase assay (Fig.1) [17], but the metabolic consequences in skeletal muscle not determined. In ovarian cancer cells, miR-144 directly regulated GLUT1 and overexpression was associated with decrease glucose uptake and glycolysis [27]. In C2C12 myotubes, IRS-1 has been proposed to be targeted by miR-128a, influencing the activity of the PI3K/Akt pathway ( Fig.…”
Section: Mirnas Affecting Insulin Signaling Pathway and Glucose Uptakementioning
confidence: 96%